The Strategic Role of Dpmptsp of East Java Province in Improving the Regional Investment Climate - Jasmine Anjani; Bayu Priambodo (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Investment growth in East Java demonstrates the contradiction between high domestic investment (PMDN) realization and low foreign direct investment (FDI), thus emphasizing the strategic importance of the DPMPTSP (Directorate General of Private Investment) in strengthening the regional investment climate. This study analyzes the role of DPMPTSP through a descriptive qualitative approach, focusing on its regulatory, administrative, and facilitative functions. The results show that the regulatory role is realized through the harmonization of central and regional policies and strengthening legal certainty through the implementation of OSS-RBA. From an administrative perspective, DPMPTSP improves service efficiency through licensing digitization and procedural simplification. Meanwhile, its facilitative role is evident in investor assistance, resolving cross-sectoral obstacles, and promoting IPRO projects. These three roles encourage increased domestic investment (PMDN), although institutional quality and regional competitiveness remain major obstacles in attracting foreign direct investment (FDI). Overall, optimizing the role of DPMPTSP is a key factor in creating a competitive and sustainable investment climate in East Java.